Pengaruh Gaya Kepemimpinan Terhadap Motivasi Kerja Pegawai Negeri Sipil di Dinas Energi Sumber Daya Mineral Sulawesi Utara - Pasla, Samuel; Mandey, Jantje; Tulusan, Femmy (Sam Ratulangi University, 2015)
ABSTRACT; Each leader has an essentially different behavior in the lead or is often called a leadershipstyle. The success of an organization supported by the role of a leader with influence in his leadershipstyle. Issues questionable in this study is the extent to which the influence of leadership styles to themotivation of civil servants working in the service of Energy Mineral resources of North Sulawesi.The methods used in this research is quantitative methods. The subject of this research is the civilservant at the Department of Energy Mineral resources of North Sulawesi. Research samples taken asmany as 20 people. Data collection is carried out using a questionnaire. Data analysis technique used is alinear regression analysis and correlation of product moment.Results of the analysis of the data indicates that the regression coefficient of the variable (X) is theleadership style of work motivation of civil servants (Y) is real and positive correlation coefficients as wellas determination and is in the category are.Based on the results of the study it can be concluded that the leadership styles influence positivelythe work motivation of civil servants, meaning that leadership style is one of the factors that determine thework motivation of civil servants.Based on the conclusions of the suggested: (1) the need for the role of the leadership to creategood communication between employees and management; (2) leaders need to give more attention toemployees who have good working performance; (3) leaders need to apply participatory leadership style inorder to create a harmonious cooperation, fosters loyalty and participation of employees.Keywords: leadership styles, motivation for work